An application of fuzzy-AHP to ship operational energy efficiency measures - Beşikçi, E. Bal; Kececi, T.; Arslan, O.; Turan, O. (Elsevier BV, 2016)
Lowering fuel consumption of ships has gained a great deal of attention in maritime industry with regards to both environmental and economic concerns. The potential for fuel economy in shipping ranging between 25% to 75% is possible by using existing technology and practices and technical improvements in the design of new ship. Despite the existence of many technology and design-based approaches, limitations of emerging these measures has led to discussions about the potential energy savings through operational changes. In this study, operational measures were examined within the scope of Ship Energy Efficiency Management Plan (SEEMP) adopted by International Maritime Organization (IMO). We applied the Analytic Hierarchy Process (Fuzzy-AHP) approach, one of multi-criteria decision making (MCDM) techniques, to prioritize the weight of each measure. Fuzzy AHP effectively reflects the vagueness of human thinking with interval values, and shows the relative importance of operational measures - which can be the fundamental decision making data for decision makers (ships' masters, operating companies and ship owners) - by providing a strategic approach to identify energy efficient solutions.
Keywords: Hydraulic engineering. Ocean engineering; Multiple criteria decision making; Fuel savings; Operational energy efficiency measures; Fuzzy AHP; Ship; TC